Mapping energy citizenship in the south of Europe - Dumitru, Adina Claudia; Losada-Puente, Luisa; Peralbo, Manuel; Brenlla, Juan Carlos; Rebollo-Quintela, Nuria; García-Fernández, Manuel (Frontiers in Psychology, 2023)
The adoption of new global approaches in the field of energy democratization requires inquiring into how people act to shape the energy system. This is where the concept of energy citizenship (ENCI) appears as a constellation of actors that enable and/or support citizens to became active participants in the debates and energy systems both in private and public sphere, or as a collective citizen that contributes to change (Pel et al., 2021). The aim of this paper is to explore the concept of ENCI in Southern Europe. Using a mixed approach, an extensive mapping of 43 ENCI initiatives in Spain (n = 29) and Portugal (n = 14) was conducted through desktop research, and a stakeholder consultation workshop (n = 7) was carried out through a focus group. Results revealed the major presence of collective ENCI types, with the citizen-based/hybrid one standing out (e.g., energy cooperatives). Most of them were motivated by the interest to contribute to energy transition or to produce and/or use renewable energy, and aimed at promoting energy saving, energy justice and reducing the carbon footprint. The general tendency is towards active participation (in Spain) and transformative forms (in Portugal). The possibilities for citizen control in the initiatives analysed is still limited. These results were confirmed by stakeholders who, additionally, pointed out the major political, social, economic, and geographical factors related to ENCI forms. In short, various types of ENCI could be validated in the Spanish and Portuguese context, showing a commitment to sustainability, democracy, and energy justice. Other non-evidenced forms may be raised as a challenge to further in-depth research on latent forms of ENCI in Southern Europe.